Interactive map of historical and archaeological sites in Makkah Almukarama - Alamri, Athmar AbdulMohsen (Journal of Humanities & Social Sciences, 2023)
The study focused on identifying historical and archaeological places in the city of Makkah in the Kingdom of Saudi Arabia, where this study aimed to infer and monitor historical and archaeological places in the city of Makkah, then establish a geographical database of historical and archaeological places using GIS technology and produce an interactive map using ArcGIS Online. To achieve the objectives of the study, a set of steps and procedures were relied upon, starting with the process of identifying historical and archaeological places based on multiple sources such as: official sources represented by the Heritage Authority (in Makkah Almukarama – Riyadh) and library sources represented in (dictionaries – history books – historical atlases), historical maps that were an informative source and mentioned many places, and field study. After extracting data from its various sources it was processed and classified into 18 classifications, namely: landmarks of the Grand Mosque, historical mosques, historical mountains, historical palaces and castles, historical houses, historical valleys, water facilities, health facilities, educational facilities, industrial facilities, rock carvings, historical tombs, holy sites, jamarat (pebbles) and historical markets, flags of the borders of the Haram and landmarks of Darb Zubaydah, building a geographical database using geographic information systems (GIS), and creating an interactive map. The study found that the number of historical and archaeological places in the holy city of Makkah amounted to 154 places, 32 places were removed, and the importance of web maps in simplifying and displaying information about historical and archaeological places, and the ease of modifying them and updating information at any time.In the light of these results, the study recommended taking advantage of the outputs of the comprehensive archaeological survey program of the territory of the Kingdom of Saudi Arabia archaeological surveys conducted since the seventies and documented in The Journal (ATLAL) until the present time in documenting archaeological and historical places in the Kingdom of Saudi Arabia with a geographical database, especially in the city of Makkah equipped with coordinates, information about them and photos; to facilitate their management and preservation, and to share them with municipalities and city development bodies to avoid the risk of their removal while carrying out various development projects, in addition to the importance of Marketing historical and archaeological places and publishing them through web maps, and installing signs on the roads to facilitate the process of access to historical and archaeological places.
Keywords: vision 2030; Historical places; Archaeological places; Makkah Almukarama; Geographic Information Systems; Interactive Map